Negative pole piece and battery
By regulating the mesoporous material content in the negative electrode active layer of the negative electrode sheet, the porosity gradient changes are achieved, and the problems of increased polarization and reduced porosity when increasing the energy density of lithium-ion batteries are solved, and the cycle life and electrochemical performance of the batteries are improved.
Patent Information
- Application Number
- CN202311818695.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2025-04-15
AI Technical Summary
In the process of increasing the energy density of existing lithium-ion batteries, it leads to increased polarization, reduced porosity, and difficulty in absorbing electrolytes, which in turn affects the cycling and electrochemical properties of the batteries, especially under low temperature or high magnification conditions.
By controlling the change in the mesoporous material content in the thickness direction of the negative electrode active layer, the porosity gradient of the negative electrode sheet is reduced from the side close to the current collector to the side far away from the current collector, improving the liquid-absorbing and liquid-retaining capacity of the negative electrode sheet to the electrolyte and balancing the battery reaction.
It reduces battery polarization, improves battery cycle life and electrochemical performance, enhances the utilization rate of negative electrode active materials, and improves the energy density and safety performance of the battery.
Smart Images

Figure CN119833570A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the field of battery technology, and in particular to a negative electrode plate and a battery. Background Art
[0002] Energy density is an important indicator for measuring the performance of lithium-ion batteries. In order to achieve high energy density, it is usually achieved by increasing the mass of active materials in the pole piece and then increasing the thickness of the dressing in the pole piece. However, this method will increase the diffusion path of lithium ions and electrons, resulting in increased polarization and aggravating the uneven polarization distribution in the thickness direction of the pole piece. In addition, this method will also reduce the porosity of the pole piece, which is not conducive to the absorption of the electrolyte, resulting in difficulty in the diffusion of the electrolyte from the surface of the pole piece to the inside, which will lead to poor battery cycle performance and reduced utilization of negative electrode active materials. Especially under low temperature or high rate conditions, the contact area between the negative electrode active material and the electrolyte is significantly reduced, and the reaction sites in the battery are correspondingly reduced, resulting in increased battery polarization and internal resistance, which greatly affects the electrochemical performance of the battery. Summary of the invention
[0003] In view of this, the present application provides a negative electrode plate and a battery, which controls the change in the content of mesoporous material in the thickness direction of the negative electrode active layer to achieve a design in which the porosity gradient of the negative electrode plate decreases from the side close to the current collector to the side away from the current collector, thereby improving the negative electrode plate's ability to absorb and retain electrolyte and balance the battery reaction, reducing battery polarization, and improving the battery cycle life and electrochemical performance.
[0004] The first aspect of the present application provides a negative electrode plate, which includes a current collector and a negative electrode active layer arranged on at least one side of the current collector, the negative electrode active layer includes a negative electrode active material, a mesoporous material, a conductive agent and a binder; wherein, in the negative electrode active layer, the mass percentage of the mesoporous material decreases from a side close to the current collector to a side away from the current collector.
[0005] In the embodiment of the present application, the mass percentage of the conductive agent increases from the side close to the current collector to the side away from the current collector, and the porosity of the negative electrode active layer decreases from the side close to the current collector to the side away from the current collector.
[0006] In an embodiment of the present application, the negative electrode active layer includes at least two stacked active sublayers; in any two adjacent active sublayers, the mass percentage of the mesoporous material in the active sublayer close to the current collector is greater than the mass percentage of the mesoporous material in the active sublayer away from the current collector.
[0007] In the embodiment of the present application, the difference in mass percentage of the mesoporous material in any two adjacent active sublayers is S, S1 / 40<S<2S1, where S1 is the mass percentage of the mesoporous material in the total mass of the negative electrode active material layer.
[0008] In the implementation manner of the present application, the number of the active sub-layers is 2-4.
[0009] In an embodiment of the present application, in the negative electrode active layer, the total mass of the mesoporous material and the conductive agent accounts for 0.1%-5% of the total mass of the negative electrode active layer; and / or the mass percentage of the mesoporous material in the total mass of the mesoporous material and the conductive agent is less than or equal to 80%.
[0010] In an embodiment of the present application, the mesoporous material includes one or more of mesoporous silica, mesoporous titania, mesoporous alumina, and mesoporous ceramics.
[0011] In the embodiment of the present application, the mesoporous material includes micropores, mesopores and macropores, wherein the volume of the mesopores accounts for 10%-95% of the total volume of the micropores, the mesopores and the macropores;
[0012] The specific surface area of the mesoporous material is 50 m 2 / g-800m 2 / g;
[0013] The particle size D50 of the mesoporous material is 10nm-1000nm.
[0014] In the embodiment of the present application, the porosity of the negative electrode plate is 20%-60%; the liquid absorption rate of the negative electrode plate is 0.1 μL / s-0.8 μL / s.
[0015] The present application designs the negative electrode plate to have a mesoporous material content that decreases gradually from the side close to the current collector to the side away from the current collector, so as to achieve a gradient change in the porosity of the negative electrode plate in the thickness direction, thereby improving the negative electrode plate's ability to absorb and retain electrode liquid and its ion diffusion capacity.
[0016] The second aspect of the present application provides a method for preparing a negative electrode sheet, comprising:
[0017] Providing at least two negative electrode slurries, each of which comprises a negative electrode active material, a mesoporous material, a conductive agent and a binder, and the contents of the mesoporous material and the conductive agent in the at least two negative electrode slurries are different;
[0018] The at least two negative electrode slurries are sequentially coated on the surface of the current collector to obtain a negative electrode active layer, wherein the mass percentage of the mesoporous material in the negative electrode active layer decreases from a side close to the current collector to a side away from the current collector.
[0019] The third aspect of the present application provides a battery, which includes a positive electrode plate, a negative electrode plate, and a separator and an electrolyte located between the positive electrode plate and the negative electrode plate, and the negative electrode plate includes the negative electrode plate provided in the first aspect of the present application or the negative electrode plate prepared by the preparation method of the negative electrode plate provided in the second aspect of the present application.
[0020] The battery provided in the present application adopts the negative electrode plate with a gradient porosity change in the thickness direction provided in the first aspect of the present application, which improves the negative electrode plate's ability to absorb and retain electrolyte and balances the battery reaction, reduces battery polarization, and improves the battery cycle life and electrochemical performance.
[0021] A fourth aspect of the present application provides an electrical device, which includes a battery as provided in the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic diagram of the cross-sectional structure of a negative electrode sheet provided in one embodiment of the present application;
[0023] Figure 2 A schematic diagram of the cross-sectional structure of a negative electrode plate provided in another embodiment of the present application.
[0024] Description of Figure Numbers
[0025] 100 - negative electrode plate; 10 - current collector; 20 - negative electrode active layer; 201 - mesoporous material; 202 - conductive agent; 21 - first active sublayer; 22 - second active sublayer; 23 - third active sublayer. DETAILED DESCRIPTION
[0026] The present application is further described in detail below in conjunction with preferred embodiments, but the protection scope of the present application is not limited to the following specific embodiments.
[0027] In the present application, all professional terms have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present application.
[0028] Energy density is an important indicator for measuring the performance of lithium-ion batteries. In order to achieve high energy density, it is usually achieved by increasing the mass of active materials in the pole piece and then increasing the thickness of the dressing in the pole piece. However, this method will increase the diffusion path of lithium ions and electrons, resulting in increased polarization and aggravating the uneven polarization distribution in the thickness direction of the pole piece. In addition, this method will also reduce the porosity of the pole piece, which is not conducive to the absorption of the electrolyte, causing the electrolyte to diffuse from the surface of the pole piece to the inside, resulting in poor battery cycle performance and reduced utilization of negative electrode active materials. Especially under low temperature or high rate conditions, the contact area between the negative electrode active material and the electrolyte is significantly reduced, and the reaction sites in the battery are correspondingly reduced, resulting in increased battery polarization and internal resistance, which greatly affects the electrochemical performance of the battery.
[0029] At present, there is a method of using multi-layer coating stepped conductive agent distribution technology to improve electrolyte diffusion and reduce battery polarization. However, this method will increase the amount of bottom conductive agent, thereby increasing the reaction active area between the negative electrode of the lithium-ion battery and the electrolyte, thereby increasing the side reactions of the battery, reducing the initial efficiency of the battery and bringing safety problems such as gas production.
[0030] In response to the above problems, the present application provides a negative electrode plate, which achieves a decrease in the porosity gradient of the negative electrode plate from the side close to the current collector to the side away from the current collector by regulating the change in the content of mesoporous material in the thickness direction of the negative electrode active layer, thereby improving the negative electrode plate's ability to absorb and retain electrolyte and balance the battery reaction, reducing battery polarization, and improving the battery cycle life and electrochemical performance.
[0031] like Figure 1 and Figure 2As shown, the present application provides a negative electrode plate 100. The negative electrode plate 100 includes a current collector 10 and a negative electrode active layer 20 disposed on at least one side of the current collector 10. The negative electrode active layer 20 includes a mesoporous material 201, a conductive agent 202, a negative electrode active material and a binder. In the embodiment of the present application, in the negative electrode active layer 20, the mass percentage of the mesoporous material 201 decreases from the side close to the current collector 10 to the side away from the current collector 10. The present application adds mesoporous material 201 to the negative electrode active layer 20. On the one hand, the addition of mesoporous material 201 optimizes the pore structure of the negative electrode sheet 100, improves the porosity of the negative electrode sheet 100, improves its ion diffusion capacity, and effectively alleviates the battery polarization phenomenon; on the other hand, the oil absorption value of the mesoporous material 201 is higher than that of the conductive agent 202. Adding mesoporous material 201 to the negative electrode sheet 100 can improve the liquid absorption and retention capacity of the negative electrode sheet for the electrolyte, avoid the problem of difficult wetting of the negative electrode sheet in the multi-layer coating process, and then improve the utilization rate of the negative electrode active material and the energy density of the battery. In addition, the structure of the mesoporous material 201 is relatively stable compared to the conductive agent, and it is not easy to react with the electrolyte. Replacing part of the conductive agent with it can effectively reduce the reactive active area between the negative electrode sheet and the electrolyte, reduce the consumption of the electrolyte, effectively inhibit the side reaction between the electrolyte and the negative electrode active material, inhibit gas production, improve the safety performance, and improve the first effect and cycle life of the battery.
[0032] In the implementation mode of this application, Figure 1 and Figure 2 As shown, in the negative electrode active layer 20, the mass percentage of the conductive agent 202 increases from the side close to the current collector 10 to the side away from the current collector 10, and the porosity in the negative electrode active layer 20 decreases from the side close to the current collector 10 to the side away from the current collector 10. The present application adjusts the content changes of the mesoporous material 201 and the conductive agent 202 in the thickness direction of the negative electrode active layer 20 to achieve a design in which the porosity gradient of the negative electrode plate 100 decreases from the side close to the current collector 10 to the side away from the current collector 10 and the electronic conductivity gradient increases, thereby simultaneously improving the ion diffusion capacity and the electrolyte absorption and retention capacity of the negative electrode plate 100, thereby improving the battery cycle life and electrochemical performance.
[0033] In the embodiment of the present application, the mesoporous material 201 may be a silicon-based mesoporous material and / or a non-silicon mesoporous material. In the embodiment of the present application, the mesoporous material 201 includes one or more of mesoporous silica, mesoporous titanium dioxide, mesoporous alumina, and mesoporous ceramics. In some embodiments of the present application, the mesoporous material 201 may be, for example, mesoporous silica. In the embodiment of the present application, the mesoporous material is a non-conductive mesoporous material with a pore size in the range of 2nm-50nm. The mesoporous material has a high specific surface area and a regular and orderly pore structure. The present application selects a mesoporous material with a porous structure and a pore size in a suitable range to be added to the negative electrode active layer, which can provide a large number of ion migration channels for the negative electrode plate and increase the contact area between the electrolyte and the negative electrode plate, thereby improving the liquid absorption and retention capacity of the negative electrode plate for the electrolyte. Compared with the conductive agent, the mesoporous material is more stable, which can effectively inhibit the side reaction between the electrolyte and the negative electrode active material, and further improve the cycle life of the battery.
[0034] In the implementation mode of the present application, the mesoporous material 201 includes micropores, mesopores and macropores. The micropores specifically refer to pore structures with a pore size of less than 2nm, the mesopores specifically refer to pore structures with a pore size of 2nm-50nm, and the macropores specifically refer to pore structures with a pore size greater than 50nm. In some implementation modes of the present application, the volume of the mesopores in the mesoporous material 201 accounts for 10%-95% of the total volume of the micropores, mesopores and macropores. In some specific embodiments of the present application, the volume of the mesopores in the mesoporous material 201 can account for 10%, 20%, 30%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% of the total volume of the micropores, mesopores and macropores. In some specific implementation modes of the present application, the volume of the mesopores in the mesoporous material 201 accounts for 40%-95% of the total volume of the micropores, mesopores and macropores. The present application controls the volume of mesopores in the mesoporous material within the above-mentioned range, thereby further controlling the porosity of the mesoporous material within an appropriate range and optimizing the pore distribution structure of the mesoporous material, thereby further improving the negative electrode's ability to absorb and retain electrolyte, thereby improving the cycle performance of the negative electrode and the energy density of the battery.
[0035] In the embodiment of the present application, the specific surface area of the mesoporous material 201 is 50 m 2 / g-800m 2 In some specific embodiments of the present application, the specific surface area of the mesoporous material 201 may be, for example, 50 m 2 / g, 60m 2 / g, 80m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g、300m2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g, 550m 2 / g、600m 2 / g, 650m 2 / g、700m 2 / g, 750m 2 / g、800m 2 / g. In the embodiment of the present application, the particle size D50 of the mesoporous material is 10nm-1000nm. In some embodiments of the present application, the particle size D50 of the mesoporous material can be, for example, 10nm, 30nm, 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm. The present application selects mesoporous materials with specific surface area and particle size within a suitable range to be added to the negative electrode active layer. The change of porosity in the negative electrode active layer can be reasonably regulated by changing the distribution of the content of the mesoporous material in the negative electrode active layer, so as to achieve a gradient change of porosity in the negative electrode active layer, effectively improve the porosity of the negative electrode plate and its ability to absorb and retain electrolyte, improve the cycle performance of the negative electrode plate and reduce polarization, thereby improving the energy density and cycle life of the battery.
[0036] In the embodiment of the present application, the negative electrode active layer 20 can be disposed on one side of the current collector 10 or on both sides of the current collector 10 according to actual application requirements. Figure 1 This is a schematic diagram of the cross-sectional structure of a negative electrode sheet 100 provided in one embodiment of the present application. In this embodiment, the negative electrode active layer 20 is disposed on one side surface of the current collector 10 . Figure 2 This is a schematic diagram of the cross-sectional structure of a negative electrode sheet 100 provided in another embodiment of the present application. In this embodiment, the negative electrode active layer 20 is provided on both side surfaces of the current collector 10. In some embodiments of the present application, the negative electrode active layer 20 can be provided on both side surfaces of the current collector 10. When the negative electrode active layer is provided on both sides of the current collector, a greater energy density can be provided for the battery, thereby improving the electrochemical performance of the battery.
[0037] In the embodiment of the present application, the negative electrode active layer 20 includes at least two stacked active sublayers. In some embodiments of the present application, the number of active sublayers may be, for example, 2, 3, or 4. In some specific embodiments of the present application, for example Figure 1As shown, the negative electrode active layer 20 includes three active sublayers stacked from the side close to the current collector 10 to the side away from the current collector 10, namely, the first active sublayer 21, the second active sublayer 22 and the third active sublayer 23. Among them, the mass percentage of the mesoporous material 201 in the first active sublayer 21, the second active sublayer 22 and the third active sublayer 23 decreases from the side close to the current collector 10 to the side away from the current collector 10; thereby, the porosity of the first active sublayer 21, the second active sublayer 22 and the third active sublayer 23 decreases from the side close to the current collector 10 to the side away from the current collector 10. The present application sets the content of the mesoporous material 201 in each active sublayer in the negative electrode active layer 20 to decrease in the direction away from the current collector 10, so that the porosity of the negative electrode active layer 20 decreases in the direction away from the current collector 10. That is to say, the gradient change design of the content of the mesoporous material in the negative electrode active layer makes the porosity of the negative electrode active layer change in a gradient, with more mesoporous material and greater porosity in the active sublayer close to the current collector, and less mesoporous material and smaller porosity in the active sublayer away from the current collector. In the negative electrode active layer 20, different active sublayers have different degrees of infiltration of the electrolyte. The addition of the mesoporous material 201 can ensure the rapid infiltration of the electrolyte into the negative electrode sheet. The present application changes the amount of mesoporous material 201 added in different active sublayers according to the degree of electrolyte infiltration of different active sublayers. It is more difficult for the electrolyte to infiltrate the active sublayer close to the current collector 10, so the content of mesoporous material 201 in the active sublayer close to the current collector 10 is higher; it is easier for the electrolyte to infiltrate the active sublayer away from the current collector 10, so the content of mesoporous material 201 in the active sublayer away from the current collector 10 is lower, which can reduce the difficulty of electrolyte infiltration of the negative electrode sheet as a whole while ensuring the conductivity of each active sublayer. The porosity gradient design can further optimize the pore structure of the negative electrode sheet, improve the infiltration and absorption effect of the negative electrode sheet on the electrolyte, increase the specific surface area, effectively alleviate the imbalance of the battery reaction, effectively reduce the concentration polarization phenomenon, and effectively improve the energy density, safety performance and cycle life of the battery.
[0038] like Figure 1In the illustrated embodiment, the mass percentage of the conductive agent 202 in the first active sublayer 21, the second active sublayer 22, and the third active sublayer 23 increases layer by layer from the side close to the current collector 10 to the side away from the current collector 10. The present application designs the content of the conductive agent 202 in each active sublayer in the negative electrode active layer 20 to increase layer by layer in the direction away from the current collector 10, that is, the content of the conductive agent in the negative electrode active layer also changes layer by layer in a direction perpendicular to the surface of the current collector, and the change trend is opposite to the layer by layer gradient change trend of the content of the mesoporous material in the negative electrode active layer. The present application designs a gradient change in the content of the conductive agent in the negative electrode active layer so that the electronic conductivity of the negative electrode active layer changes according to a gradient layer by layer. The active sublayer close to the current collector has less conductive agent and lower electronic conductivity, while the active sublayer far from the current collector has more conductive agent and higher electronic conductivity. The gradient design of electronic conductivity can balance the electronic conductivity and ionic conductivity, thereby effectively alleviating the imbalance of the battery reaction, thereby reducing polarization and improving the energy density and electrochemical performance of the battery.
[0039] In the implementation manner of the present application, the difference in the mass percentage of the mesoporous material in any two adjacent active sublayers is S, S1 / 40<S<2S1, where S1 is the mass percentage of the mesoporous material in the total mass of the negative electrode active material layer. The present application controls the difference in the mass percentage of the mesoporous material in adjacent active sublayers within a suitable range, that is, controls the rate of change of the porosity of the active sublayer in the negative electrode active layer within a suitable range, which can make the effect of the gradient change more obvious, the battery reaction more balanced, effectively avoid the occurrence of polarization phenomenon, and further improve the battery cycle life and energy density.
[0040] In the embodiment of the present application, in the negative electrode active layer 20, the total mass of the mesoporous material 201 and the conductive agent 202 accounts for 0.1%-5% of the total mass of the negative electrode active layer 20. In some embodiments of the present application, in the negative electrode active layer 20, the total mass of the mesoporous material 201 and the conductive agent 202 may account for 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1.0%, 1.3%, 1.5%, 1.8%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0% of the total mass of the negative electrode active layer 20. In the embodiment of the present application, the mass percentage of the mesoporous material 201 to the total mass of the mesoporous material 201 and the conductive agent 202 is less than or equal to 80%. In some embodiments of the present application, the mass percentage of the mesoporous material 201 in the total mass of the mesoporous material 201 and the conductive agent 202 can be, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%. In some specific embodiments of the present application, the total mass of the mesoporous material 201 and the conductive agent 202 in each active sublayer of the negative electrode active layer 20 is equal, and the mass of other components in each active sublayer of the negative electrode active layer 20, such as the negative electrode active material, the binder, etc., except the mesoporous material 201 and the conductive agent 202, is also equal. By controlling the total mass of the mesoporous material and the conductive agent in each active sub-layer of the negative electrode active layer to the same value, and controlling the mass of other components except the mesoporous material and the conductive agent to the same value, the present application can achieve a gradient change in the mass percentage of the mesoporous material and the mass percentage of the conductive agent in the negative electrode active layer by only adjusting the ratio between the mesoporous material and the conductive agent, thereby achieving a gradient change in the porosity and electronic conductivity in the negative electrode active layer, optimizing the pore structure of the negative electrode plate, reducing polarization, and enhancing the negative electrode plate's ability to absorb and retain electrolyte, thereby improving the energy density and cycle life of the battery.
[0041] In some embodiments of the present application, the porosity of the negative electrode sheet can be, for example, 20%, 23%, 25%, 28%, 30%, 32%, 34%, 35%, 36%, 38%, 40%, 42%, 45%, 48%, 50%, 55%, 60%; the liquid absorption rate of the negative electrode sheet can be, for example, 0.1 μL / s, 0.15 μL / s, 0.2 μL / s, 0.2 2μL / s, 0.24μL / s, 0.25μL / s, 0.26μL / s, 0.28μL / s, 0.3μL / s, 0.32μL / s, 0.34μL / s, 0.35μL / s, 0.36μL / s, 0.38μL / s, 0.4μL / s, 0.5μL / s, 0.6μL / s, 0.7μL / s, 0.8μL / s. The present application improves the porosity of the negative electrode sheet by introducing mesoporous materials, and optimizes the pore distribution structure of the negative electrode sheet by regulating the content of the mesoporous materials in each active sublayer in the negative electrode active layer; and the addition of mesoporous materials in the negative electrode active layer and the gradient change of their content significantly improve the liquid absorption and retention capacity of the negative electrode sheet for the electrode liquid.
[0042] The negative electrode plate provided in the present application is designed by regulating the content of mesoporous material in the thickness direction of the negative electrode active layer to achieve a design in which the porosity gradient of the negative electrode plate decreases from the side close to the current collector to the side away from the current collector, thereby improving the negative electrode plate's ability to absorb and retain electrolyte and balance the battery reaction, reducing battery polarization, and improving the battery cycle life and electrochemical performance.
[0043] The present application also provides a method for preparing a negative electrode sheet, comprising:
[0044] S101, providing at least two negative electrode slurries, each of the negative electrode slurries comprising a negative electrode active material, a mesoporous material, a conductive agent and a binder, and the contents of the mesoporous material and the conductive agent in the at least two negative electrode slurries are different;
[0045] S102. Apply the at least two negative electrode slurries sequentially on the surface of the current collector to obtain a negative electrode active layer, so that the mass percentage of the mesoporous material in the negative electrode active layer decreases from the side close to the current collector to the side away from the current collector, and the mass percentage of the conductive agent increases from the side close to the current collector to the side away from the current collector, so as to obtain a negative electrode sheet.
[0046] In step S101, the number of types of negative electrode slurry is greater than or equal to 2. In some embodiments of the present application, the number of types of negative electrode slurry may be, for example, 2, 3 or more.
[0047] In the embodiments of the present application, the mesoporous material may be a silicon-based mesoporous material and / or a non-silicon-based mesoporous material. In some embodiments of the present application, the mesoporous material includes one or more of mesoporous silica, mesoporous titania, mesoporous alumina, and mesoporous ceramics.
[0048] In the embodiments of the present application, the conductive agent may be any conductive agent known in the art. In some embodiments of the present application, the conductive agent may be, for example, one or more of super P-Li, super P, acetylene black, graphene, and carbon nanotubes.
[0049] In the embodiments of the present application, the negative electrode active material may be any negative electrode active material known in the art for use in lithium-ion batteries, including but not limited to one or more of carbon-based negative electrode active materials, silicon-based negative electrode active materials, tin-based negative electrode active materials, and lithium metal negative electrode active materials. In some embodiments, the carbon-based negative electrode may include but is not limited to one or more of materials such as graphite, carbon fiber, hard carbon, soft carbon, mesophase carbon microspheres, and graphene; the silicon-based negative electrode may include but is not limited to one or more of materials such as elemental silicon, silicon carbide, silicon oxide, silicon metal compounds, and composite silicon materials; the tin-based negative electrode may include but is not limited to one or more of materials such as elemental tin, tin carbide, tin oxide, and tin metal compounds. In the embodiments of the present application, the negative electrode active material includes but is not limited to the above examples.
[0050] In the embodiments of the present application, the binder may be any binder known in the art. In some embodiments of the present application, the binder may be, for example, one or more of styrene-butadiene rubber and polyvinylidene fluoride.
[0051] In some embodiments of the present application, the negative electrode slurry further includes a thickener, and the thickener may be any thickener known in the art. In some embodiments of the present application, the thickener may be, for example, sodium hydroxycellulose.
[0052] In some embodiments of the present application, in the negative electrode slurry, the mass percentage of the negative electrode active material is greater than or equal to 78.5%, the mass percentage of the mesoporous material is greater than or equal to 0.1% and less than or equal to 5%, the mass percentage of the conductive agent is greater than 0 and less than or equal to 6.5%, the mass percentage of the binder is greater than 0 and less than or equal to 5%, and the mass percentage of the thickener is greater than 0 and less than or equal to 5%.
[0053] In step S102, the current collector may be any negative electrode current collector known in the art. In some embodiments of the present application, the current collector may be, for example, copper foil. In the embodiments of the present application, the negative electrode slurry may be applied to the surface of one side of the current collector, or to the surfaces of both sides of the current collector, according to actual application requirements.
[0054] The preparation method of the negative electrode sheet provided in the present application is simple in process, and the content of the mesoporous material in the negative electrode active layer of the prepared negative electrode sheet changes in a gradient along the direction perpendicular to the surface of the current collector through the multi-layer coating technology, thereby making the porosity of the negative electrode sheet change in a gradient along the direction perpendicular to the surface of the current collector. The negative electrode sheet prepared by the method has good liquid absorption and retention ability for the electrolyte, effectively avoids battery polarization, and has a long battery cycle life and good electrochemical performance.
[0055] The present application also provides a battery, which includes a positive electrode plate, a negative electrode plate, and a diaphragm and an electrolyte located between the positive electrode plate and the negative electrode plate, and the negative electrode plate includes the negative electrode plate provided above. In the embodiment of the present application, the battery includes but is not limited to lithium-ion batteries and sodium-ion batteries. In some embodiments of the present application, the battery is a lithium-ion battery, and the positive electrode active material in the positive electrode plate is but is not limited to one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium phosphate containing olivine structure. In the embodiment of the present application, the diaphragm is but is not limited to a composite film of one or more of polyethylene, polypropylene, and polyvinylidene fluoride.
[0056] The present application also provides an electric device, which includes the battery provided above. The electric device may be, for example, an electric car, a mobile phone, a tablet computer, a laptop computer, a wearable device (a watch, a bracelet), a digital camera, etc.
[0057] The present application is further described below in multiple embodiments:
[0058] Example 1
[0059] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed with deionized water in a mass ratio of 96:0.05:0.95:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on a copper foil by a coating machine to prepare a double-sided substrate;
[0060] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:0.95:0.05:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0061] Example 2
[0062] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber and the deionized water are uniformly mixed in a mass ratio of 96:0.1:0.9:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on a copper foil by a coating machine to prepare a double-sided substrate;
[0063] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, and the binder styrene-butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:0.9:0.1:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0064] Example 3
[0065] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed with deionized water in a mass ratio of 96:0.15:0.85:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on a copper foil by a coating machine to prepare a double-sided substrate;
[0066] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:0.85:0.15:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0067] Example 4
[0068] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber and the deionized water are uniformly mixed in a mass ratio of 96:0.2:0.8:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on a copper foil by a coating machine to prepare a double-sided substrate;
[0069] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, and the binder styrene-butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:0.8:0.2:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0070] Example 5
[0071] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed with deionized water in a mass ratio of 96:0.25:0.75:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on a copper foil by a coating machine to prepare a double-sided substrate;
[0072] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:0.75:0.25:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0073] Example 6
[0074] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber and the deionized water are uniformly mixed in a mass ratio of 96:0.3:0.7:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on the copper foil by a coating machine to prepare a double-sided substrate;
[0075] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:0.7:0.3:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0076] Example 7
[0077] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed with deionized water in a mass ratio of 96:0.35:0.65:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on a copper foil by a coating machine to prepare a double-sided substrate;
[0078] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, and the binder styrene-butadiene rubber are uniformly mixed with deionized water in a mass ratio of 96:0.65:0.35:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0079] Example 8
[0080] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber and the deionized water are uniformly mixed in a mass ratio of 96:0.4:0.6:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on the copper foil by a coating machine to prepare a double-sided substrate;
[0081] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:0.6:0.4:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0082] Example 9
[0083] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed with deionized water in a mass ratio of 96:0.45:0.55:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on a copper foil by a coating machine to prepare a double-sided substrate;
[0084] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene-butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:0.55:0.45:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0085] Example 10
[0086] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber and the deionized water are uniformly mixed in a mass ratio of 96:0.4:0.6:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on the copper foil by a coating machine to prepare a double-sided substrate;
[0087] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed with deionized water in a mass ratio of 96:0.5:0.5:1:2 to form a middle layer negative electrode slurry, and the middle layer negative electrode slurry is coated on the double-sided substrate coated with the bottom layer negative electrode slurry by a coating machine;
[0088] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:0.6:0.4:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom and middle negative electrode slurries by a coating machine to obtain a negative electrode sheet.
[0089] Embodiment 11
[0090] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous aluminum oxide, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber and the deionized water are uniformly mixed in a mass ratio of 96:0.45:0.55:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on a copper foil by a coating machine to prepare a double-sided substrate;
[0091] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous aluminum oxide, the thickener sodium hydroxycellulose, and the binder styrene-butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:0.55:0.45:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0092] Example 12
[0093] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber and the deionized water are uniformly mixed in a mass ratio of 96:0.2:0.8:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on a copper foil by a coating machine to prepare a double-sided substrate;
[0094] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, and the binder styrene-butadiene rubber are mixed evenly with deionized water in a mass ratio of 96.2:0.2:0.6:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0095] Comparative Example 1
[0096] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber and the deionized water are uniformly mixed in a mass ratio of 96:0.5:0.5:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on a copper foil by a coating machine to prepare a double-sided substrate;
[0097] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, and the binder styrene-butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:0.5:0.5:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0098] Comparative Example 2
[0099] The negative electrode active material graphite, the conductive agent super P-Li, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed with deionized water in a mass ratio of 96:1:1:2 to form a negative electrode slurry, and the negative electrode slurry is coated on both sides of the copper foil by a coating machine to prepare a double-sided substrate;
[0100] The negative electrode active material graphite, the conductive agent super P-Li, the thickener sodium hydroxycellulose, and the binder styrene-butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:1:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0101] Comparative Example 3
[0102] The negative electrode active material graphite, mesoporous silica, thickener sodium hydroxycellulose, binder styrene butadiene rubber are mixed with deionized water in a mass ratio of 96:1:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on a copper foil by a coating machine to prepare a double-sided substrate;
[0103] The negative electrode active material graphite, mesoporous silica, thickener sodium hydroxycellulose, and binder styrene-butadiene rubber are evenly mixed with deionized water in a mass ratio of 96:1:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry using a coating machine to obtain a negative electrode sheet.
[0104] Comparative Example 4
[0105] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed with deionized water in a mass ratio of 96:0.95:0.05:1:2 to form a bottom negative electrode slurry, and the bottom negative electrode slurry is coated on a copper foil by a coating machine to prepare a double-sided substrate;
[0106] The negative electrode active material graphite, the conductive agent super P-Li, the mesoporous silica, the thickener sodium hydroxycellulose, the binder styrene butadiene rubber are mixed evenly with deionized water in a mass ratio of 96:0.05:0.95:1:2 to form an upper negative electrode slurry, and the upper negative electrode slurry is coated on the double-sided substrate coated with the bottom negative electrode slurry by a coating machine to obtain a negative electrode sheet.
[0107] Liquid absorption and retention capacity test
[0108] Liquid absorption rate test: The negative electrode sheets prepared in the embodiments and comparative examples were spread flat on the test platform of the contact angle meter, the amount of electrolyte droplets (5 μL) was fixed, the electrolyte was dropped on the surface of the negative electrode sheet, and the timing was started. The electrolyte droplets were observed with the naked eye through a microscope until they disappeared, the time taken for the disappearance process was recorded, and the liquid absorption rate was calculated. The calculation formula for the liquid absorption rate was: liquid absorption rate = liquid droplet amount / droplet disappearance time.
[0109] Liquid holding capacity test: the negative electrode sheets prepared in the embodiments and comparative examples were baked at 120°C for 12 h, and the mass of the negative electrode sheets after baking was recorded. Under a 25°C environment, the baked negative electrode sheets were immersed in the electrolyte for 24 h and then taken out, and the mass of the negative electrode sheets after being immersed in the electrolyte was recorded. The liquid holding capacity of the negative electrode sheets was calculated, and the calculation formula for the liquid holding capacity is: Liquid holding capacity = (mass of the negative electrode sheet after being immersed in the electrolyte - mass of the negative electrode sheet after baking) / mass of the coating of the negative electrode sheet.
[0110] Porosity measurement
[0111] The negative electrode sheets prepared in the embodiments and comparative examples are placed in a mercury intrusion tester, the test container is filled with mercury, and the pressure is continuously applied to press the mercury into the gaps in the negative electrode sheets. The amount of mercury intrusion displayed by the equipment is read out, and the porosity of the negative electrode sheets is calculated. The calculation formula for the porosity of the negative electrode sheets is: porosity = mercury intrusion amount / volume of the negative electrode sheet coating.
[0112] Resistivity test
[0113] The negative electrode sheets prepared in the embodiment and the comparative example are laid flat in the test chamber of the resistance meter, and the test probe is brought into contact with the surface of the negative electrode sheet to perform the test, and the resistivity of the negative electrode sheet is read from the instrument computer.
[0114] Electrochemical performance test
[0115] The positive electrode active material lithium iron phosphate, the conductive agent epoxy, the binder polyvinylidene fluoride and N-methyl pyrrolidone are uniformly mixed in a mass ratio of 96:1:3, and coated on an aluminum foil by a coating machine to prepare an integrated positive electrode sheet;
[0116] The negative electrode sheets, positive electrode sheets and separators prepared in Examples 1-12 and Comparative Examples 1-4 were respectively prepared into 2Ah stacked batteries in the order of positive electrode sheet, separator and negative electrode sheet, and their initial charge and discharge efficiency, rate charge and discharge capability and cycle performance were tested respectively.
[0117] Full battery first test:
[0118] At 25°C, the battery was charged at 0.1C constant current and constant voltage to 100% SOC, aged at 45°C for 24h, and discharged at 0.1C constant current to 0% SOC. The charging capacity and discharging capacity were recorded, and the first charge and discharge efficiency was calculated. The first efficiency of the whole battery = discharge capacity / charge capacity*100%.
[0119] The charge and discharge ratio test conditions are:
[0120] At 25°C, the battery was charged to 100% SOC at 0.1C, left for 30 min, and then discharged to 0% SOC at 4C. The discharge efficiency was calculated as follows: discharge efficiency = discharge capacity at 3C rate / discharge capacity at 0.1C.
[0121] At 25°C, the battery was charged to 100% SOC at 4C, left for 30 min, and then discharged to 0% SOC at 0.1C. The charging efficiency was calculated as follows: charging efficiency = charging capacity at 3C rate / charging capacity at 0.1C.
[0122] The cycle test conditions are: 25°C, charge and discharge at 1C, calculate the capacity retention rate, capacity retention rate = current cycle discharge capacity / first cycle discharge capacity, compare the number of battery cycles under the same capacity retention rate.
[0123] Table 1 Related properties of negative electrode sheets and batteries prepared in Examples 1-12 and Comparative Examples 1-4
[0124]
[0125]
[0126] It can be seen from the data in Table 1 that the present application controls the amount of mesoporous material added to each active sublayer in the negative electrode active layer and the ratio between the two to achieve a gradient change in the porosity in the negative electrode sheet along the direction perpendicular to the current collector. It can be seen from Examples 1-9 that when the mass percentage of the mesoporous material in the negative electrode sheet to the total mass of the mesoporous material and the conductive agent is controlled at the same value, the greater the difference in the mass percentage of the mesoporous material in the adjacent active sublayers to the total mass of the mesoporous material and the conductive agent, the faster the liquid absorption rate of the corresponding negative electrode sheet, and the stronger the absorption capacity of the electrolyte, but the difference in the mass percentage of the mesoporous material in the adjacent active sublayers to the total mass of the mesoporous material and the conductive agent has little effect on the liquid retention capacity of the negative electrode sheet, and the liquid retention capacity of the negative electrode sheets of Examples 1-9 is maintained at a relatively high value.
[0127] Compared with Comparative Example 2 in which no mesoporous material is added or Comparative Example 1 and Comparative Example 3 in which the content of the mesoporous material does not change in a gradient, the battery obtained by the negative electrode sheets prepared in Examples 1-12 has both excellent liquid absorption and retention performance and electrochemical performance. And it can be seen from Comparative Example 4 that the content of the mesoporous material in the negative electrode sheet presents a gradient change opposite to that of the embodiment of the present application, and the liquid absorption and retention capacity and electrochemical performance of the obtained battery for the electrolyte are lower than those of the embodiment of the present application.
[0128] The preferred embodiments are described in detail above, but the present invention is not limited to the above-mentioned specific implementation modes. Under the guidance of the present application, technicians in this field can also make various specific changes without departing from the scope of protection of the present application, which all fall within the scope of protection of the present invention.
Claims
1. A negative electrode plate, characterized in that: The negative electrode plate comprises a current collector and a negative electrode active layer disposed on at least one side of the current collector, wherein the negative electrode active layer comprises a negative electrode active material, a mesoporous material, a conductive agent and a binder; Wherein, in the negative electrode active layer, the mass percentage of the mesoporous material decreases from the side close to the current collector to the side away from the current collector.
2. The negative electrode sheet according to claim 1, characterized in that: The mass percentage of the conductive agent increases from the side close to the current collector to the side away from the current collector; and / or the porosity of the negative electrode active layer decreases from the side close to the current collector to the side away from the current collector.
3. The negative electrode sheet according to claim 1 or 2, characterized in that: The negative electrode active layer includes at least two stacked active sublayers; in any two adjacent active sublayers, the mass percentage of the mesoporous material in the active sublayer close to the current collector is greater than the mass percentage of the mesoporous material in the active sublayer away from the current collector.
4. The negative electrode sheet according to claim 3, characterized in that: The difference in mass percentage of the mesoporous material in any two adjacent active sublayers is S, S1 / 40<S<2S1, where S1 is the mass percentage of the mesoporous material in the total mass of the negative electrode active material layer.
5. The negative electrode sheet according to claim 3 or 4, characterized in that: The number of the active sublayers is 2-4.
6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: In the negative electrode active layer, the total mass of the mesoporous material and the conductive agent accounts for 0.1%-5% of the total mass of the negative electrode active layer; and / or the mass percentage of the mesoporous material in the total mass of the mesoporous material and the conductive agent is less than or equal to 80%.
7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The mesoporous material includes one or more of mesoporous silica, mesoporous titania, mesoporous alumina and mesoporous ceramics.
8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: The mesoporous material includes micropores, mesopores and macropores, wherein the volume of the mesopores accounts for 10%-95% of the total volume of the micropores, the mesopores and the macropores; The specific surface area of the mesoporous material is 50 m 2 / g-800m 2 / g; The particle size D50 of the mesoporous material is 10nm-1000nm.
9. The negative electrode sheet according to any one of claims 1 to 8, characterized in that: The porosity of the negative electrode plate is 20%-60%; the liquid absorption rate of the negative electrode plate is 0.1 μL / s-0.8 μL / s.
10. A method for preparing a negative electrode sheet, characterized in that: include: Providing at least two negative electrode slurries, each of which comprises a negative electrode active material, a mesoporous material, a conductive agent and a binder, and the mesoporous material content in the at least two negative electrode slurries is different; The at least two negative electrode slurries are sequentially coated on the surface of the current collector to obtain a negative electrode active layer, wherein the mass percentage of the mesoporous material in the negative electrode active layer decreases from a side close to the current collector to a side away from the current collector.
11. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, and a separator and an electrolyte located between the positive electrode sheet and the negative electrode sheet. The negative electrode sheet comprises the negative electrode sheet as described in any one of claims 1 to 9 or a negative electrode sheet prepared by the method for preparing a negative electrode sheet as described in claim 10.
12. An electrical device, characterized in that: The electric device comprises the battery as claimed in claim 11.